Across Punjab - Compiled by Naazish Ata-Ullah,Prof. [et al.] (Lahore, Pakistan Topical Printer, Lahore)
About Punjab Culture etc.
Include Color Illustration
Allaiance Francaise, Annmarie Haus Schimmel German Cultural Center Associated with Goethe-Institute and National College of Ars Lahore Pakistan
Keywords: Punjab -- Pakistan--Punjab